Preparation of YbAlN piezoelectric thin film by sputtering and influence of Yb concentration on properties and crystal structure - Uehara, Masato; Amano, Yuki; Anggraini, Sri Ayu; Hirata, Kenji; Yamada, Hiroshi; Akiyama, Morito (Ceramics international, 2021)
Aluminum nitride (AlN) is a key material for piezoelectric micro-electromechanical systems (MEMS). Since the discovery of the increase in AlN piezo performance by scandium (Sc) doping, many groups have investigated other effective dopants. However, another effective single dopant has not yet been experimentally demonstrated, although potential effectiveness has been indicated by theoretical calculations. In this study, we propose ytterbium (Yb) as an effective dopant. The sputtering conditions for YbxAl1 − xN films were optimized by design of experiments (DoE). Consequently, high-quality YbxAl1 − xN films were obtained. YbxAl1 − xN with x values ranging from 0 to 0.37 demonstrate good piezo response. A maximum d33 of ~12 pC/N, which is approximately twice the value of non-doped AlN, is achieved. According to crystallographic analysis using X-ray diffraction, the influence of Yb concentration on the crystal structure was similar to that of Sc with differences observed at high Yb concentration.